Psychophysiological reactivity to sleep-related emotional stimuli in primary insomnia. - Baglioni, C; Lombardo, C; Bux, E; Hansen, S; Salveta, C; Biello, S; Violani, C; Espie, C (2010)
The present study examined psychophysiological reactivity to emotional stimuli related and non-related to sleep in people with primary insomnia (PPI) and in good sleepers (GS). Twenty-one PPI and 18 GS were presented with five blocks of neutral, negative, positive, sleep-related negative and sleep-related positive pictures. During the presentation of the pictures, facial electromyography (EMG) of the corrugator and the zygomatic muscles, heart rate (HR) and cardiac vagal tone (CVT) were recorded. Subjective ratings of the stimuli were also collected. We found that only PPI exhibited greater inhibition of the corrugator activity in response to sleep-related positive stimuli compared to the other blocks of stimuli. Furthermore, PPI rated the sleep-related negative stimuli as more unpleasant and arousing and showed higher CVT in response to all stimuli as compared to GS. Results were interpreted as indicating that PPI exhibit craving for sleep-related positive stimuli, and also hyper-arousability in response to sleep-related negative stimuli, as compared to GS. Our results suggest that psychological treatment of insomnia could benefit by the inclusion of strategies dealing with emotional processes linked with sleep processes.